Tackling the Issue of Student Motivation Through Educational Technology: An Action Research Model - Steel, John; Holden, Graham (Proceedings of the International Conference on Networked Learning, 2000)
As part of broader research at Sheffield Hallam University which seeks to explore student and tutors perceptions and experiences of networked learning and educational technologies (Steel and Hudson, 2000), this paper presents findings that focus more narrowly on specific issues around the learning and teaching experience of one member of staff and his students. Following an action research model (Kemmis, 1997), this paper explores the process of change within the restructuring of a level one unit in which problems of student attainment and motivation were identified. This paper explores both the lecturer's understanding of learning technologies with regard to how such technologies might help solve the problems of poor attainment and motivation; and the students own perceptions of how networked learning and the use of educational technologies might contribute to an 'enriched learning experience' for them. The first part of the paper will outline the lecturers expectations, experiences and process of reflection (Schon, 1987) relative to his engagement with networked learning technologies; particularly in relation to the notion of increasing the quality of the student learning experience thus tackling the problem of attendance and retention. The second part of the paper will explore the student perspective of this process, particularly in relation to their perceptions and experiences of networked learning and educational technologies within their course of study, but also within higher education in general. In providing an insight into the perceptions and experiences of the lecturer and his students within this context, we provide an example of a methodological framework that seeks to be proactive in engaging staff and students in exploring ways to enhance and enrich their learning and teaching experience, thus providing a remedy to the problems noted above. In addition, we offer an account of an innovative use of learning technology with which practitioners may be able to draw from within their own learning and teaching contexts.